2016
DOI: 10.4212/cjhp.v69i1.1517
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Systems-Based Intervention to Improve IV Hydration during Parenteral Administration of Acyclovir

Abstract: Background: Intravenous (IV) hydration is considered a protective factor in reducing the incidence of acyclovir-induced nephrotoxicity. A systemsbased review of cases of acyclovir-associated acute kidney injury can be used to examine institution-, care provider-, and task-related factors involved in administering the drug and can serve as a basis for developing a quality improvement intervention to achieve safer administration of acyclovir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“… 44 , 60 The remaining 38 studies (83%) 32 34 , 36 40 , 42 , 45 58 , 61 66 , 68 76 applied an observational study design without large magnitude of effect, which is why they were graded as low quality. Controlled low-quality studies (n = 31) applied variable designs: simulation studies (n = 11) 32 34 , 36 39 , 49 , 53 , 57 , 66 ; observational reviews of drug charts, medication orders, or patient records (n = 11) 45 47 , 51 , 52 , 68 70 , 74 76 ; studies combining multiple methods (n = 4) 56 , 58 , 61 , 72 ; analyses of medication error or adverse drug event data (n = 3) 40 , 42 , 55 ; and analyses of infusion concentrations (n = 2). 48 , 50 Some low-quality studies (n = 7) 54 , 62 – 65 , 71 , 73 used an uncontrolled study design.…”
Section: Resultsmentioning
confidence: 99%
“… 44 , 60 The remaining 38 studies (83%) 32 34 , 36 40 , 42 , 45 58 , 61 66 , 68 76 applied an observational study design without large magnitude of effect, which is why they were graded as low quality. Controlled low-quality studies (n = 31) applied variable designs: simulation studies (n = 11) 32 34 , 36 39 , 49 , 53 , 57 , 66 ; observational reviews of drug charts, medication orders, or patient records (n = 11) 45 47 , 51 , 52 , 68 70 , 74 76 ; studies combining multiple methods (n = 4) 56 , 58 , 61 , 72 ; analyses of medication error or adverse drug event data (n = 3) 40 , 42 , 55 ; and analyses of infusion concentrations (n = 2). 48 , 50 Some low-quality studies (n = 7) 54 , 62 – 65 , 71 , 73 used an uncontrolled study design.…”
Section: Resultsmentioning
confidence: 99%
“…Also, acyclovir aldehyde metabolite may cause direct renal tubular insult leading to acyclovir induced renal toxicity ( Whitley et al, 1982 ). Isotonic hydration has been shown to decrease the risk of IV acyclovir induced renal toxicity ( Kim and Byun, 2015 , Dubrofsky et al, 2016 , Pacheco et al, 2005 , Whitley et al, 1982 ). However, we could not find this in the present study, probably since the great majority had been given IV hydration.…”
Section: Discussionmentioning
confidence: 99%
“…It is a purine nucleoside synthetic agonist that converts to an active metabolite called acyclovir triphosphate that exhibits antiviral activity against HSV type 1, HSV type 2 and varicella-zoster virus ( Kłysik et al, 2020 , Cortesi and Esposito, 2008 ). The primary route of elimination is via the kidneys through glomerular filtration and renal tubular secretion, with a half-life in the body ranging from 2 to 3 h and up to 20 h depending on renal function ( Cortesi and Esposito, 2008 , Dubrofsky et al, 2016 ). Renal intratubular deposition of acyclovir crystals or acyclovir direct tubular toxicity are major mechanisms behind nephrotoxicity in patients treated with intravenous (IV) acyclovir ( Chang et al, 2016 , Izzedine et al, 2005 , Yildiz et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, after rapid or excessive intravenous infusion, ACV becomes crystallized and forms precipitation in the renal tubules due to its low water solubility, which blocks the tubules, thus causing acute renal failure [49]. A recent study reported that the incidence of nephrotoxicity caused by ACV was 18-21% [54]. The renal function could be partially restored after ACV discontinuation.…”
Section: Nephrotoxicity and Neurotoxicitymentioning
confidence: 99%